Spheres of liberty : changing perceptions of liberty in American culture - Kammen, Michael G. (Curti lectures, 2001)
Liberty, one of the most consequential words in our language, is one of the most treasured concepts in American thought--and one of the most intensely debated. Its meaning is constantly shifting, changing not only from one culture to another but also, over time, within the same culture. No two definitions of liberty seem alike. In this subtle and illuminating work Michael Kammen traces the evolving concept of liberty throughout American history and provides a solid framework for understanding the meaning of the term today. He shows that by the early seventeenth century a tension between libert.